Stock portfolio and optimal return - Sartika Sartika (Yayasan Widyantara Nawasena Raharja, 2023)
The lifting of restrictions on community activities (or PPKM) gave a positive signal to the capital market, especially listed firms in the transportation and logistics sector. This study aims to compile an investment portfolio in order to obtain optimal returns and make estimates for the next 120 days. The sample used in this study is obtained from observations on 1 January 2023 to 30 April 2023. This study uses the Treynor ratio to determine which stocks have a better risk-return trade-off. The results of the analysis using ARIMA show that TRJA has a high return and risk, while TMAS and ELPI have the highest return with low risk. *This article has been presented at Master of Accounting: Best Kolokium Award